2015
DOI: 10.3329/bjmed.v26i2.25449
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pattern of Liver Abscess among the Patients Admitted in Rajshahi Medical College Hospital

Abstract: Introduction: Liver abscess is an important clinical problem in tropical regions of the world. Current assessment of liver abscesses should allow for better understanding of the aetiopathogenesis of the disease. This study was conducted to find the clinical pattern and aetiopathogenesis of liver abscess in patients admitted in Rajshahi Medical College Hospital. Methodology: The present cross-sectional study was carried out in the Department of Medicine, Rajshahi Medical College Hospital (RMCH) on consecutive 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…6,7 Similarly our study did not correlate with some other studies. 8,9 In our study we found male to female ratio 8:1 which was similar to others. 6,9 Most of the patient are economically poor and lives in rural area.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…6,7 Similarly our study did not correlate with some other studies. 8,9 In our study we found male to female ratio 8:1 which was similar to others. 6,9 Most of the patient are economically poor and lives in rural area.…”
Section: Discussionsupporting
confidence: 92%
“…In our study pus culture were negative in 66% of patient, but previous study showed 70% was negative. 6,8 The major advantages of percutaneous needle aspiration are: 1) it is less invasive and less expensive; 2) avoids problems related to catheter care; and 3) multiple abscess cavities can be aspirated easier in the same setting. 14 The success rate of percutaneous needle aspiration in the literature varies from 77-100%.…”
Section: Discussionmentioning
confidence: 99%